Peran Teman Sebaya dalam Menumbuhkan Adversity Quotient Santri - Layts Layyin Mubarakah; Novia Fetri Aliza (Islamic Counseling: Jurnal Bimbingan dan Konseling Islam, 2023)
Living life in an Islamic boarding school is not an easy thing for teenagers. The difficulties experienced by teenagers at Islamic boarding schools are certainly very different from the difficulties experienced by teenagers outside Islamic boarding schools. During the observations, the author found several cases where there were santri (Islamic Boarding School Students) who had run away from the Islamic boarding school with the aim of being expelled, but the students still continued to live in the Islamic boarding school. Another fact, is that there are students who violate the regulations in Islamic boarding schools with the same goal, namely to get them expelled from the Islamic boarding school, but in fact the students still remain in the Islamic boarding school. The aim of this research is to examine in more depth the role of peer support in growing the Adversity Quotient in Santri. As well as knowing the role of peers for students at the Raudhatus Salaam Islamic boarding school. This research uses a qualitative descriptive method using a phenomenological approach with case studies. The author's data collection method uses interview techniques, documentation and also field observation. The subjects in this study were 5 students who had low Adversity Quotien experience, namely, CPR, RARK, H, INAF, and RF. The results of the research show that the Adversity Quotient description of the students at the Raudhatus Salaam Islamic boarding school is fairly good. This shows that the students are able to control themselves when they have problems. Meanwhile, regarding the role of peer support in growing the Adversity Quotient in this research, it has an important role. The factors that support students to remain in Islamic boarding schools in this research are the support of friends and the environment. Meanwhile, the inhibiting factors are friend problems and also financial problems.